Indonesia’s War on Illegal Fishing: Impact on China - Zhang, Hongzhou (2015)
Indonesia’s war on illegal fishing, particularly by foreign fishing vessels in Indonesian waters, has not only resulted in huge costs to China’s fishing industry. It has also cast a shadow on the future prospect of China’s Maritime Silk Road Initiative and Indonesia’ Global Maritime Fulcrum ambition.